BLACK SWANS ANOMALIES TESTING ON INDONESIA STOCK EXCHANGE - Christianto, Eman; Murhadi, Werner Ria (Journal of Management and Business, 2016)
This Research aim to know Black Swan Anomalies happen in BEI to stock indexes LQ45 make overreaction and make price reversal and winner-loser anomalies. to test abnormal return use One Sample T-test and to know overreaction so make price reversal and winner-loser anomalies use Paired Sample T-Test. Based on result and discussion concluded that Black Swan Anomalies come on in BEI for stock indexes and effect Black Swan Anomalies are bleed and blowup make happen overreaction so make price reversal and winner-loser anomalies happen in BEI for stock indexes LQ45.